A case of severe endogenous endophthalmitis with orbital cellulitis post Covid-19 - Letsoalo, Herold L.; Mathebula, Solani D. (AOSIS, 2022)
Coronavirus disease 2019 (COVID-19) is a novel pandemic viral illness which may lead to severe respiratory diseases. However, its ophthalmic manifestations are still not well understood. There could be serious complications involving various organs in patients with the disease and in those who are recovering, or have recovered, from COVID-19. Endogenous endophthalmitis, was a rare occurrence in the past but has increased in the post-COVID-19 pandemic. Endogenous endophthalmitis results from hematogenous spread from a remote primary source. A 55-year-old man with confirmed COVID-19 presented to a local hospital with unilateral gradual loss of vision and swelling of the left eye that occurred 10 days after discharge from the hospital. Based on detailed ophthalmic examination, this patient with a co-morbidity, namely diabetes mellitus was placed in the intensive care unit where he was given corticosteroids and ventilation for two weeks. Most patients requiring mechanical ventilation may experience disorders of the eye, and it may be difficult to treat these occurrences while the patient remains in ICU. COVID-19 can lead to ocular complications especially in the late stages of infection. Follow-up of post COVID-19 patients is crucial to monitor possible ocular complaints including endophthalmitis as early diagnosis and treatment is essential to salvage vision. Contribution: There is a possible link between COVID-19 and endophthalmitis, which is a rare but devastating eye infection. The medical community should consider the eye when evaluating the role of anti-infectious treatment and immunomodulation.
Journal article published in Journal of African Vision and Eye Health
Keywords: 2019 Coronavirus; Corticosteroids; Covid-19; Endogenous endophthalmitis; Orbital cellulitis; Coronavirus infections; COVID-19 (Disease); Adrenocortical hormones